2011
DOI: 10.5897/ajb11.156
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium content in leaf and root of oat (Avena sativa L.) grown on pseudogley soil

Abstract: Acid soils are not suitable for cultivation of agricultural crops as increased concentrations of hydrogen ions hinder the uptake of most nutrients. The adverse effects of increased soil acidity also include release of aluminium (Al) ions from the adsorption complex and hence, an increase in their concentration in the soil solution and plants. Aluminium ions block phosphorus and potassium uptake by the crop, thus leading to disturbance of plant growth and development, as well as to a substantial decline in crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Al ions blocked K + uptake in oat (6) and in soybean plants (7) . Al reduced the absorption of K + in four species of coffee (8) .…”
Section: Introductionmentioning
confidence: 91%
“…Al ions blocked K + uptake in oat (6) and in soybean plants (7) . Al reduced the absorption of K + in four species of coffee (8) .…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, P deficiency is a major concern in acidic soils as Al has a high affinity to P and forms insoluble Al-P compounds in soils (Magalhaes et al, 2018). Numerous studies have reported that Al reduces P uptake and utilization in several plant species such as Eucalyptus (Teng et al, 2018), oat (Avena sativa) (Djuric et al, 2011), Citrus grandis (Guo et al, 2017) and soybean (Chen et al, 2019b). These studies indicate that Al toxicity results in plant nutritional imbalance, which can affect the growth and productivity of crops.…”
Section: Reduction Of Water and Nutrient Uptakementioning
confidence: 99%
“…depths would be expected if gypsum (CaSO 4 ) was added to the soil (Shainberg et al, 1989), instead of only lime (CaCO 3 ). According to Djuric et al (2011), the main effect of soil acidity is Al 3+ toxicity, with the Al 3+ saturation (m) index being the best measure to assess this component of soil acidity and indicates the percentage of the effective soil cation exchange capacity (t) that is occupied by Al 3+ . Differences were found (p < 0.05) between treatments regarding Al 3+ saturation (Table 2) at 0-0.2 and 0.2-0.4 m soil depth.…”
mentioning
confidence: 99%